Exposure to closed-loop scrubber washwater alters biodiversity, reproduction, and grazing of marine zooplankton - Jönander, Christina; Egardt, Jenny; Hassellöv, Ida-Maja; Tiselius, Peter; Rasmussen, Matilda; Dahllöf, Ingela (Frontiers in Marine Science, 2023)
Shipping is a large industry responsible for atmospheric emissions of hazardous substances including SOX, NOX, and particulate matter. Many ships have installed exhaust gas cleaning systems (scrubbers) to remove primarily SOX from the exhaust, but the hazardous substances are instead transferred to the water used in the scrubbing process. Ships with closed-loop scrubbers recirculate the water but can still discharge around 126-150 m3 directly to the surrounding marine environment every day. The discharged water contains metals and organic substances, such as polycyclic aromatic hydrocarbons, that are known to be toxic to marine zooplankton. Here we show that closed-loop scrubber washwater is toxic to communities of marine mesozooplankton at our lowest tested dilution, 1.5% (v/v), and affects survival, reproduction, diversity, and ability to predate on microzooplankton. The cumulative toxic unit of the undiluted closed-loop scrubber washwater was estimated to 17, which indicates that the water could be toxic at levels below what was tested in this study. Among all detected substances, vanadium, copper, benzo[ghi]perylene, nickel, and zinc were identified as toxicity-driving substances in the order listed. Closed-loop scrubber washwater has been shown to affect development and survival in single species of copepods, but here we find evidence of toxicity at the community level, irrespective of seasonal community structure, and that the exposure has potential to disrupt the interactions between trophic levels in the pelagic food web. We show that the closed-loop scrubber washwater cause both lethal and sublethal effects in marine zooplankton, due to contaminants, some of which are persistent in the marine environment.